2011
DOI: 10.1586/eci.11.65
|View full text |Cite
|
Sign up to set email alerts
|

Alternate roles for immune regulators: establishing endometrial receptivity for implantation

Abstract: Many immune regulators are now identified as having key roles at the embryo-maternal interface. Importantly, a cohort of cytokines, chemokines and growth factors are produced by the endometrial glands and secreted into the uterine cavity where they act both on the blastocyst and on the endometrial surface, changing adhesive capacity, modifying blastocyst development and outgrowth and providing chemoattraction, in addition to their previously known functions in immune regulation. As implantation progresses to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 119 publications
0
17
0
1
Order By: Relevance
“…Cytokines and chemokines have been shown to play key roles during early implantation events [26][30] and their receptors are abundantly expressed by human trophoblast [11][13], [31]. Previously we and others have demonstrated that CCL2, 5, and 7 and CX3CL1 are produced by a variety of cell types in the maternal endometrium and have key local actions important for implantation including leukocyte infiltration and trophoblast trafficking [9], [10], [12], [20], [32].…”
Section: Discussionmentioning
confidence: 98%
“…Cytokines and chemokines have been shown to play key roles during early implantation events [26][30] and their receptors are abundantly expressed by human trophoblast [11][13], [31]. Previously we and others have demonstrated that CCL2, 5, and 7 and CX3CL1 are produced by a variety of cell types in the maternal endometrium and have key local actions important for implantation including leukocyte infiltration and trophoblast trafficking [9], [10], [12], [20], [32].…”
Section: Discussionmentioning
confidence: 98%
“…Details of the specific mechanisms by which known candidates are involved in distinct stages of complex trophoblast-endometrial interactions have been described previously (251). Of the ligands and receptors described in this review, cytokines and chemokines are perhaps the most intriguing signaling ligands in this respect, and more emphasis on these factors is likely to dominate future research (252). Their complementary expression in both the implanting blastocyst and receptive endometrium (LIF, CSFs, etc) ( Figure 2) is highly suggestive of a functional role in the early stages of adhesion, blastocyst anchorage and orientation, and controlled immune suppression to facilitate invasion.…”
Section: Potential Mechanisms Of Implantationmentioning
confidence: 93%
“…56 Selectins play an important role in leukocyte transendothelial trafficking by mediating leukocyte rolling on the surface of endothelia, 57 and a similar effect of L-selectins on blastocyst apposition to the endometrial epithelium has been suggested. 41,58 As L-selectin is associated with lymphocyte extravasation during inflammation, circulating L-selectin levels may be increased during autoimmune inflammation in patients with type 1 diabetes 59 and Graves disease. 60 L-selectin is also a potential antigenic target because autoantibodies to L-selectin have been described in murine lupus.…”
Section: Adhesion Moleculesmentioning
confidence: 99%